Construction of Law Regarding The Role of The Regional Government In Providing Incentives For Micro Businesses Through Equity Crowdfunding - Sari, Shinta Puspita (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The policy complementary to regional investment is governed in Article 278 of Law Number 23 of 2014 and Government Regulation Number 24 of 2019. The availability of incentives and supporting facilities, however, remain to be the problems amidst shrinking regional budgets following the pandemic affecting economic sectors. The Regional Government of Batu City, among others, has perceived this effect and is on its way to reviving micro businesses to back up the local tourism.Purposes of the Research: This research aims to find out and analyze the role of the Regional Government in providing incentives for micro businesses through equity crowdfunding.Methods of the Research: This research employed normative-juridical methods with research data collected from library research and Focus Group Discussion discussed held in the Regional Government of Batu.Results of the Research: The regulatory framework in Batu city regarding micro businesses complies with Regional Regulation Number 1 of 2016, implying that the operation of the Integrated Business Services Center (PLUT) serves as a vital aspect in the development of Micro, Small, and Medium Enterprises (MSMEs) in Batu, and this is expected to help develop the MSMEs in the city. The regulation also implies that the local government is responsible for funding MSMEs by providing grants, requesting international funds, giving incentives that ease permit requirements, reducing tariffs imposed on infrastructure and facilities, and other forms of incentive. Existing potentials and opportunities must be used to enhance the capacity of human resources as the facilitators at PLUT in Batu.